Delaying quality changes in ‘Namdokmai Sithong’ mango fruit during low-temperature storage using trisodium phosphate - Ganjana, R.; Kramchote, S.; Laosinwattana, C. (My University, 2024)
This study explored the efficacy of trisodium phosphate (TSP) in maintaining the postharvest quality of ‘Namdokmai Sithong’ mangoes under low-temperature storage conditions. Employing a completely randomized design, mangoes were treated with TSP at 0 (control), 0.25, 0.50, and 0.75 g L-1 and stored at 6±2°C with 85±5% RH for 25 days. Quality assessments, conducted every five days, focused on firmness, peel color, total soluble solids (TSS), hydrogen peroxide (H2O2), titratable acidity (TA), and phenolic content. Results showed that while TSP did not influence firmness, it significantly delayed peel color changes and affected TSS, H2O2, TA, and phenolic levels. The 0.50 and 0.75 g L-1 concentrations were most effective, with no marked difference between them, suggesting a recommendation of 0.50 g L-1 TSP for optimal cost-efficiency in preserving mango quality.
Keywords: antioxidants; GRAS chemical substances; peel color; postharvest quality; reactive oxygen species; Thai mango